Incidence of bleeding in patients on different anticoagulants and antiplatelet therapies undergoing thoracentesis. Issue 1 (19th July 2021) - Aljundi, Lamia; Chaar, Abdelkader; Boshara, Peter; Shiari, Aryan; Gennaoui, George; Noori, Zaid; Girard, Cristine; Szpunar, Suzan; Franco-Elizondo, Rene
Abstract : Introduction: Thoracentesis is one of the most commonly performed procedures in the inpatient setting. Although coagulation profile is usually evaluated prior to thoracentesis, bleeding is a rare complication, occurring in less than 1% of the cases. Several society guidelines recommend holding antiplatelet medications and anticoagulants prior to thoracentesis. Clinical practice guidelines also recommend correcting international normalised ratios of more than two and platelet counts <50 X10 ∧ 9/L. Methods: This is a retrospective descriptive study that included 292 patients who underwent thoracentesis in the inpatient setting at Ascension St John Hospital in Detroit, Michigan, USA from 2016 to 2018. We identified patients who had uncorrected risk for bleeding and collected data about their demographics, comorbidities, use of antiplatelet or anticoagulants and procedural details including complications. We looked for any postprocedural bleeding events to study their relation to the already established bleeding risk. Results: Two hundred and ninety-two thoracenteses were performed, 95.5% (n=279) were performed by interventional radiology. Majority of patients were at risk of bleeding 83% (n=242). No bleeding events occurred. Medications that were not held prior to thoracentesis included: clopidogrel 11% (n=32), novel anticoagulants 8.2% (n=24) and unfractionated heparin 50% (n=146). Use of ultrasound guidance decreased the amount of haemoglobin decline from 1 to 2 g/L (p=0.029). Seventeen patients suffered pneumothorax, eight of which required intervention. Discussion: Our study suggests that performing thoracentesis without correction of underlying coagulopathy may be safe. This may prevent consequences of holding essential medications and reduce the amount of blood products administered to patients in need of thoracentesis.